Romanian prehistoric archaeology, between tradition and innovation - Enea, S.-С. (Археологія і давня історія України, 2012)
With this text, the author intends to present a short history of the evolution of Romanian prehistoric archaeology, from the moment of its appearance in the 19th century to the present day. Thus, several distinct stages that mark this evolution have been detected, stages influenced by the charisma and activity of certain personalities. It can be noticed that the scientific foundations of this discipline were laid after World War I by Vasile Pârvan, the founder of Romanian archaeology, whose followers have dominated the scientific discourse to this day. Romanian prehistoric archaeology, just like other areas of historical research, mirrored the political discourse, and, unfortunately, was under its sway during certain periods of time. Целью статьи было представить краткую историю эволюции румынской доисторической археологии, с момента своего становления в 19 веке и по сей день. Были вычленены несколько различных этапов этой эволюции зависящие как от общего уровня уровня развития археологии так и от харизмы и деятельности отдельных личностей. Очевидно, что научные основы дисциплины были заложены после Второй мировой войны Василием Парваном, основателем археологии Румынии, последователи которого доминируют в научном дискурсе по сей день. Румынская доисторическая археология, как и другие области исторического исследования, отражалась в политическом дискурсе, и, к сожалению, находилась под его влиянием в течение определенного периода времени.